2006
DOI: 10.1161/01.hyp.0000242336.58387.1f
|View full text |Cite
|
Sign up to set email alerts
|

NO Modulates NADPH Oxidase Function Via Heme Oxygenase-1 in Human Endothelial Cells

Abstract: Abstract-NO is known to induce expression of heme oxygenase-1, an antioxidant enzyme in blood vessels. We tested whether NO might modulate the endothelial NADPH oxidase function via heme oxygenase-1. In human microvascular endothelial cells, the NO donor DETA-NONOate (0.1 to 1 mmol/L) strongly induced expression of heme oxygenase-1 but not Cu/Zn superoxide dismutase. This was associated with a reduction of the superoxide-generating capacity of NADPH oxidase, an effect that depended on de novo gene transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
88
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 36 publications
10
88
0
Order By: Relevance
“…However, in the present study it was observed that cellular levels of the key heme-containing Nox subunits present in endothelium, other subunits thought to regulate the Nox oxidases investigated, and Cu,Zn-SOD were not altered by the increased HO-1 expression elicited by exposure to NO. 1 These data on the absence of detectible changes in Nox oxidase expression also rule out another recently reported mechanism 5 involving NO donors inhibiting the expression of mRNA for Nox1. Thus, the superoxide-depressing effects of exposure of endothelium to NO seemed to be associated with an increased HO-1 activity and not with an alternative antioxidant action of NO or a change in the expression of Cu,Zn-SOD or key components of Nox oxidases present in endothelium.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…However, in the present study it was observed that cellular levels of the key heme-containing Nox subunits present in endothelium, other subunits thought to regulate the Nox oxidases investigated, and Cu,Zn-SOD were not altered by the increased HO-1 expression elicited by exposure to NO. 1 These data on the absence of detectible changes in Nox oxidase expression also rule out another recently reported mechanism 5 involving NO donors inhibiting the expression of mRNA for Nox1. Thus, the superoxide-depressing effects of exposure of endothelium to NO seemed to be associated with an increased HO-1 activity and not with an alternative antioxidant action of NO or a change in the expression of Cu,Zn-SOD or key components of Nox oxidases present in endothelium.…”
supporting
confidence: 64%
“…Regulation by protein kinase C-p47 phox is likely to activate Nox oxidases containing Nox1 or Nox2 but not the Nox4 subunits 8 of the oxidases, which are observed to be present in the endothelial cells studied. 1 Overall, the results of the study of Jiang et al 1 support a mechanism shown in the Figure according to which prolonged exposure to NO elicits increased expression of HO-1, and the generation of bilirubin, resulting from the metabolism of heme by this enzyme, attenuates Nox oxidase-derived superoxide production by preventing oxidase activation by p47 phoxdependent pathways. Based on previous work in the literature demonstrating the potential importance of NO x in increasing the expression of HO-1 and the redox stress-associated regulation of transcriptional activation of this gene, 2,3 NO x derived from the reaction of superoxide with NO or the oxidation of NO are likely to mediate the increase in HO-1 expression caused by prolonged exposure of endothelium to NO.…”
mentioning
confidence: 64%
“…Phycorubins are similar in activity to bilirubin, which is ubiquitously found in mammalian systems and actively inhibits the translocation of p47 phox to the plasma membrane (144,210). The obvious advantage of using compounds that are converted to bilirubin is their oral bioavailability.…”
Section: Phycobilinsmentioning
confidence: 99%
“…The antioxidant properties of this enzyme are mediated largely via intracellular generation of free bilirubin, which functions physiologically to inhibit certain NADPH oxidase complexes [43][44][45][46]. Intriguingly, in a massive prospective study in the UK, serum levels of bilirubin at baseline were found to correlate inversely with risk for both COPD and lung cancer, after controlling for smoking habit [47].…”
Section: Complementary Protection From Spirulina?mentioning
confidence: 99%